THE IMPLEMENTATION OF QUANTUM LEARNING MODEL USING SOCIAL-SPIRITUAL VALUE THROUGH LESSON STUDY TO IMPROVE SOCIAL-SPIRITUAL ATTITUDES AND LEARNING RESULTS OF SCIENCE II BASIC CONCEPT - Astawan, I Gede; Sudana, Dewa Nyoman (Universitas Pendidikan Ganesha, 2018)
The research objectives were (1) to improve the social-spiritual attitudes of students through the application of quantum learning models containing social-spiritual values through lesson study. (2) To improve the learning outcomes of students' basic science II science concepts through the application of quantum learning models containing social-spiritual values through lesson study. The method used to achieve the above objectives is the method of action research. The data collected were social-spiritual attitudes with questionnaires and the learning outcomes the basic concepts of science II with tests. The data analysis technique used is descriptive statistics. The research findings are (1) the application of quantum learning models containing social-spiritual values through lesson study can improve students' social-spiritual attitudes. This can be seen increasing from cycle I to cycle II at 13.28%. (2) Application of quantum learning models containing social-spiritual values through lesson study can improve learning outcomes of students' basic science II concepts. This can be seen increasing from cycle I to cycle II at 12.25%. Based on the findings of this study, it is recommended that teachers / lecturers use the quantum learning model with the value of social-spiritual attitudes as an alternative to innovative learning models in order to improve the social-spiritual attitudes and learning outcomes of students. Further researchers are advised to examine in a relatively longer time to see the effectiveness of the quantum learning model with the value of social-spiritual attitudes in improving the social-spiritual attitudes and learning outcomes of students